2013
DOI: 10.4070/kcj.2013.43.2.87
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Implication of Metabolic Syndrome in Patients with Heart Failure

Abstract: Background and ObjectivesMetabolic syndrome (MetS) increases the risk of heart failure (HF). The purpose of this study was to identify the prevalence of MetS in patients with HF and determine the syndrome's association with HF in clinical and laboratory parameters.Subjects and MethodsA total of 3200 HF patients (67.6±14.5 years) enrolled in a nationwide prospective Korea HF Registry between Jan. 2005 and Oct. 2009. Patients were divided into two groups according to the presence or absence of MetS at admission:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…However, there are still great controversies about the impact of MS on the prognosis in patients with established HF. Some studies had reported that HF patients with MS had a significantly reduced risk of in-hospital mortality ( 9 ), as well as long-term all-cause mortality ( 10 , 11 ), compared with HF patients without MS. However, such association was not documented in other studies ( 12 , 13 ), raising concern of whether such “epidemiologic paradox” was true in the HF–MS relationship.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still great controversies about the impact of MS on the prognosis in patients with established HF. Some studies had reported that HF patients with MS had a significantly reduced risk of in-hospital mortality ( 9 ), as well as long-term all-cause mortality ( 10 , 11 ), compared with HF patients without MS. However, such association was not documented in other studies ( 12 , 13 ), raising concern of whether such “epidemiologic paradox” was true in the HF–MS relationship.…”
Section: Introductionmentioning
confidence: 99%
“…There was no relation suggested by Mets to uncontrolled BP group. It can be explained by the risk profile of subjects requiring three or more drugs and coronary artery disease patients too different to be compared with the most populations where Mets implied cardiovascular risk [ 16 ]. Smoking was usually known to be associated with elevation of daytime BP or masked HT.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the effect of the TyG index on the prognosis of HF patients was more prominent in the MetS group, which was confirmed by our study. What is more, extracardiac comorbidities (including obesity, hypertension, diabetes, and MetS) affect a high proportion of HFpEF patients [ 42 , 43 ]. Finally, although it is suggested that HFmrEF may be a transitional state between HFpEF and HFrEF [ 44 ], patients with HFmrEF have clinical features and prognoses that are more similar to those of patients with HFpEF than those of patients with HFrEF [ 45 ].…”
Section: Discussionmentioning
confidence: 99%